Dual Designated Path Routing Algorithm For Congestion Control In High-Density Network - Subramaniam, Siva Kumar; Azman, Amierul Syazrul; Ikhwan Lee, Mohamad Yusry Lee; Feroz, Farah Shahnaz (Little Lion Scientific Islamabad Pakistan, 2021)
Wireless sensor networks (WSNs) offer promising and flexible solutions in a wide range of industrial applications, particularly in the oil and gas downstream pipeline. Such an application requires wide communication coverage due to the large dissemination of pipelines in the downstream sector and to fit this requirement, the nodes have to be arranged in a grid formation. Performance evaluation has been carried out using reactive (e.g., AODV) and proactive (e.g., OLSR) routing protocol during the early of the study. Several issues have been discovered as the network size increases, mainly due to the increased loads, which occupy the queue and congest the network traffic. These issues include packet loss, throughput degradation, energy wastage, and poor fair share of network resources. The OEG reactive routing algorithm is proposed to lessen the routing instabilities by reducing the control packets and promoting smoother packets flow through the traffic division into odd-path and even-path with the consideration of x and y-axis. The proposed routing algorithm was then compared to AODV and OLSR routing algorithm in terms of network performance. The proposed routing algorithm has shown notable improvements on the delivery ratio (28.4% more), throughput (13.6 kbps more), fairness index (0.02 more), passive nodes' presence (37.9% less), and energy consumption (0.76 J less) when solely compared to AODV on the highest network density.